Seasonal and Event-related Fluctuations in the Positivity of the Language in Sir Walter Scott’s Journal - Whissell, Cynthia (Advances in Social Sciences Research Journal, 2020)
Computerized sentiment analysis based on the Dictionary of Affect in Language (Whissell, 2009) was employed to assess patterns in the employment of positive (pleasant) language in the journal kept by Sir Walter Scott between 1825 and 1832. The continuous portion of the journal (33 months) was modeled with a polynomial regression. Two major patterns were observed. In the earlier portions of the journal, significant seasonal variations were present, with more positively toned entries in the Spring/Summer and less positive ones in the Fall/Winter. In the later portions of the journal there were discontinuities most likely attributable to ill health; significantly greater emotional variability was noted with some of the least positive entries occurring at about the time when Scott was facing his final illness and just before he stopped making journal entries.